A review on future wastewater treatment technologies: micro-nanobubbles, hybridelectro-Fenton processes, photocatalytic fuel cells, and microbial fuel cells - Nurhafizah, Mohd Selihin; Tay, Meng Guan (2022)
The future prospect in wastewater treatment technologies mostly emphasizes processing efficiency and the economic benefits. Undeniably,the use of advanced oxidation processes in physical and chemical treatments has played a vital role in helping the technologies to removethe organic pollutants efficiently and reduce the energy consumption or even harvesting the electrons movements in the oxidation process toproduce electrical energy. In the present paper, we review several types of wastewater treatment technologies, namely micro-nanobubbles,hybrid electro-Fenton processes, photocatalytic fuel cells, and microbial fuel cells. The aims are to explore the interaction of hydroxyl radicalswith pollutants using these wastewater technologies, including their removal efficiencies, optimal conditions, reactor setup, and energy gen-eration. Despite these technologies recording high removal efficiency of organic pollutants, the selection of the technologies is dependent onthe characteristics of the wastewater and the daily production volume. Hence the review paper also provides comparisons between tech-nologies as the guidance in technology selection.